Pengembangan Media Pembelajaran menggunakan Microsoft Sway dalam Pembelajaran Pendidikan Pancasila pada Siswa Kelas IV Sekolah Dasar - Rahmadani, Dina; Rahmatina, Rahmatina (TSAQOFAH, 2025)
The limited use of information technology-based instructional media and the lack of media variety in schools underscore the need for innovative teaching tools that align with current technological developments. This study aims to develop an interactive learning medium based on Microsoft Sway, which has undergone validation, practicality testing, and effectiveness testing for use in Grade IV Civic Education (Pendidikan Pancasila) classes at the elementary school level. The research employed a Research and Development (R&D) approach using the ADDIE development model, comprising five phases: analysis, design, development, implementation, and evaluation. Data were collected through validation questionnaires completed by subject matter, language, and media experts, as well as practicality questionnaires completed by teachers and students. The trial subjects included 13 fourth-grade students from SDN 25 Sungai Tarab, while the main study subjects were 13 students from SDN 26 Gurun. Validation results indicated the media was highly valid, with scores of 90% (content), 82.5% (language), and 96.15% (media). Practicality tests showed very high levels of practicality: 92.85% (teachers) and 96.97% (students) at the trial school, and 96.42% and 97.80% at the main research school. Effectiveness testing results were also very high, with scores of 88.46% and 94.61%, respectively. The study concludes that Microsoft Sway-based instructional media is valid, practical, and effective in enhancing the quality of Pendidikan Pancasila learning for Grade IV elementary school students.